Short term health-related quality of life improvement during opioid agonist treatment. (1st December 2015) - Nosyk, B.; Bray, J.W.; Wittenberg, E.; Aden, B.; Eggman, A.A.; Weiss, R.D.; Potter, J.; Ang, A.; Hser, Y.-I.; Ling, W.; Schackman, B.R.
Highlights: We examine short-term health utility of patients on opioid agonist treatment (OAT). OAT initially improves health utility across all treatment modalities and patients. Health utility subsequently decreases slightly or increases at diminished rate. Results suggest a threshold level in health-related quality of life response to OAT. Abstract: Background: Opioid dependence is associated with high levels of morbidity, yet sparse data exists regarding the health-related quality of life (HRQoL) of individuals with opioid dependence, particularly following treatment initiation. To inform cost-effectiveness analyses of treatment modalities, this study investigates short-term changes in HRQoL following enrollment into opioid agonist treatment (OAT), across treatment modalities and patient subgroups. Methods: Data was analyzed from the Starting Treatment with Agonist Replacement Therapies (START) and Prescription Opioid Addiction Treatment Studies (POATS) randomized controlled trials. Participants included individuals dependent on prescription opioids (POs) or heroin, receiving limited-term or time-unlimited treatment. PO- or heroin-users in START received buprenorphine/naloxone (BUP/NX) or methadone (MET) over 24 weeks. PO-users in POATS received psychosocial care and short-term (4-week) taper with BUP/NX, with non-responders offered subsequent extended (12-week) stabilization and taper. HRQoL was assessed using the short-form SF-6D while in and out of OAT, with distinction between MMT and BUP/NX in START. Linear mixed effects regression models were fitted to determine the independent effects of OAT on HRQoL and characterize HRQoL trajectories. Results: Treatment had a similar immediate and modest positive association with HRQoL in each patient subgroup. The association of OAT on HRQoL was statistically significant in each model, with effect sizes between 0.039 (heroin-users receiving BUP/NX) and 0.071 (PO-users receiving MET). After initial improvement, HRQoL decreased slightly, or increased at a diminished rate. Conclusions: OAT, whether delivered in time-limited or unlimited form, using BUP/NX or MET, is associated with modest immediate HRQoL improvements, with diminishing benefits thereafter.